The effect of industry concentration on financial statement comparability - Elhoshy, Mohamed Mahmoud; Zaytoun, Mohamed Khamis (Edelweiss Applied Science and Technology, 2025)
This study investigates the effect of industry concentration on financial statement comparability. The analysis is based on a sample of 553 firm-year observations from 79 non-financial companies listed on the Egyptian Stock Exchange between 2016 and 2022. Using regression analysis, the findings demonstrate a statistically significant negative relationship between industry concentration and financial statement comparability. This suggests that as industry concentration increases, corporate transparency tends to decline, as managers in highly concentrated industries have more discretion in making accounting and reporting choices. Such discretion can reduce financial statement comparability across firms. These conclusions are supported by robustness checks using alternative measures for both industry concentration and comparability. The study adds to the existing literature by providing insights into how the competitive environment influences firms’ accounting policies and reporting strategies, which in turn affects the quality and comparability of financial reporting. By highlighting the relationship between industry concentration and financial transparency, the research offers practical implications for investors seeking more informed decisions and emphasizes the importance of regulatory efforts to ensure the production of high-quality, comparable financial statements—particularly in industries with high concentration levels.